Transcription Factor-Induced Lineage Programming of Noradrenaline and Motor Neurons from Embryonic Stem Cells. (19th February 2014) - Mong, Jamie; Panman, Lia; Alekseenko, Zhanna; Kee, Nigel; Stanton, Lawrence W.; Ericson, Johan; Perlmann, Thomas
Abstract : An important goal in stem cell biology is to develop methods for efficient generation of clinically interesting cell types from relevant stem cell populations. This is particularly challenging for different types of neurons of the central nervous system where hundreds of distinct neuronal cell types are generated during embryonic development. We previously used a strategy based on forced transcription factor expression in embryonic stem cell-derived neural progenitors to generate specific types of neurons, including dopamine and serotonin neurons. Here, we extend these studies and show that noradrenergic neurons can also be generated from pluripotent embryonic stem cells by forced expression of the homeobox transcription factor Phox2b under the signaling influence of fibroblast growth factor 8 (FGF8) and bone morphogenetic proteins. In neural progenitors exposed to FGF8 and sonic hedgehog both Phox2b and the related Phox2a instead promoted the generation of neurons with the characteristics of mid- and hindbrain motor neurons. The efficient generation of these neuron types enabled a comprehensive genome-wide gene expression analysis that provided further validation of the identity of generated cells. Moreover, we also demonstrate that the generated cell types are amenable to drug testing in vitro and we show that variants of the differentiation protocols can be applied to cultures of human pluripotent stem cells for the generation of human noradrenergic and visceral motor neurons. Thus, these studies provide a basis for characterization of yet an additional highly clinically relevant neuronal cell type. Stem Cells 2014;32:609–622